Neuroprotective Strategies in Repair and Replacement of the Aortic Arch - Manetta, Frank; Mullan, Clancy W.; Catalano, Michael A. (International Journal of Angiology, 2018)
Aortic arch surgery is a technical challenge, and cerebral protection during distal anastomosis is a continued topic of controversy and discussion. The physiologic effects of hypothermic arrest and adjunctive cerebral perfusion have yet to be fully defined, and the optimal strategies are still undetermined. This review highlights the historical context, physiological rationale, and clinical efficacy of various neuroprotective strategies during arch operations.
Keywords: aorta; aortic aneurysm; cerebral perfusion; circulatory arrest; hypothermia